Predictors of survival in children born with spina bifida. (7th June 2011) - Tennant, P W G; Pearce, M S; Bythell, M; Rankin, J
Abstract : Background: Spina bifida is associated with life-long disability and reduced survival, but the determinants of survival for those born with spina bifida remain poorly understood. This study describes the impact of several factors on the survival of children born with spina bifida, up to age 10 years. Methods: Cases of isolated spina bifida, delivered during 1985–2003, were identified from the population-based Northern Congenital Abnormality Survey (NorCAS). Survival status was determined from local and national mortality records. Cox regression models were used to examine the potential influences of survival. Results: 500 cases of spina bifida were identified during the study, a prevalence of 7.5 (95% CI 6.9 to 8.2) per 10 000 total births. 10-year survival among live born cases was 66.6% (95% CI 59.8 to 72.6), increasing significantly with time (p=0.002) from 60.2% (95% CI 51.1 to 68.0) in 1985–1990 to 83.3% (95% CI 64.5 to 92.7) in 1997–2003. The proportion of terminations of pregnancy also increased from 40.2% (95% CI 34.0 to 46.6) in 1985–1990 to 72.4% (95% CI 64.5 to 79.3) in 1997–2003 (p<0.001). The presence of hydrocephalus significantly reduced survival (p<0.001) from a 10-year survival of 86.7% (95% CI 77.7 to 92.2) among cases without hydrocephalus to 53.3% (95% CI 43.3 to 62.3) among cases with hydrocephalus. Gestational age (p<0.001) predicted survival but birth weight, socio-economic status, maternal age, or infant sex, did not. Conclusions: Survival of children born with spina bifida has improved significantly over time, but prognosis remains poor for children born with hydrocephalus or preterm. These data are important for counselling families and for health service planning.